Patterns of general and abdominal obesity and their association with hypertension control in the iranian hypertensive population: insights from a nationwide study - Fataneh Esmaeili; Keyvan Karimi; Samaneh Akbarpour; Mohammadreza Naderian; Shirin Djalalinia; Ozra Tabatabaei-Malazy; Ali Golestani; Nazila Rezaei (BMC Public Health)
Abstract Background The coexistence of obesity and hypertension (HTN) is a global health concern due to its association with various health abnormalities. This study targeted the association between uncontrolled HTN—defined according to the JNC8 guidelines— and different obesity patterns (general and abdominal) among adult hypertensive individuals. Methods Data for the present investigation were obtained from the 2021 STEPwise Approach to NCD Risk Factor Surveillance (STEPS) national survey in Iran. Participants were classified based on general obesity (BMI) and different abdominal obesity patterns (waist circumference [WC], waist-to-hip ratio [WHR], and waist-to-height ratio [WHtR]). Data were weighted by sex, age, and residence (rural and urban). Multivariate logistic regression models were performed to determine the association between different obesity patterns and uncontrolled HTN, adjusting for confounders including demographic variables, lifestyle factors, and history of metabolic abnormalities. Results A total of 8,692 hypertensive adult subjects ≥ 18 years were recruited from all provinces in Iran. The overall mean age of participants was 55.8 ± 0.15, and 55.6% being women. The prevalence of general obesity among controlled and uncontrolled hypertensive patients was 30.3% and 69.8%, respectively. Regarding abdominal obesity, the prevalence among controlled and uncontrolled hypertensive patients was 29.8% and 70.2% based on WC, 28.4% and 71.6% based on WHR, and 28.8% and 71.2% based on WHtR, respectively. Compared to normal weight, underweight (adjusted odds ratio [AOR] = 0.94, 95% CI: 0.57–1.56), overweight (1.37 [1.16–1.61]), and general obesity (1.47 [1.24–1.75]) were associated to uncontrolled HTN compared to normal weight. Abdominal obesity according to WC (1.30 [1.13–1.51]), WHR (1.31 [1.10–1.53]), and WHtR (1.39 [1.11–1.74]) was also associated with uncontrolled HTN. Conclusion Both general and abdominal obesity are more prevalent and strongly associated with uncontrolled HTN in hypertensive patients. These findings underscore the need for healthcare providers to implement targeted interventions promoting healthy lifestyle changes to mitigate these risk factors and improve HTN management.